Evaluation Of Work Plans And Budgets In Improving The Quality Of Financial Statements At The Central Papua Provincial Inspectorate - Anita Datu Sanggalangi; Corvis L Rantererung; Johannes Baptista Halik (Jurnal Inovasi Global, 2025)
The evaluation of the Work Plan and Budget (PRKA) is essential in improving the quality of financial reports at the Central Papua Provincial Inspectorate. This study aims to analyze how PRKA evaluation contributes to enhancing the quality of financial reports. Using a qualitative approach, the research collected both primary and secondary data through observation, interviews, and documentation. Informants included 10 finance department employees. Data analysis was conducted using qualitative descriptive techniques, involving data reduction, presentation, and drawing conclusions. The findings reveal that the PRKA implementation is structured through stages from planning to accountability, emphasizing transparency, accountability, and budget efficiency. Strict supervision is a key factor in preventing irregularities. Supporting elements for high-quality financial reports include adherence to accounting standards, competent human resources, effective financial systems, and a strong culture of transparency and accountability. The evaluation of PRKA ensures proper budget allocation and utilization, reinforcing the transparency, accountability, and efficiency of financial management practices. The study concludes that PRKA evaluation is a critical process for promoting effective and accountable financial governance within local government institutions. The implications of this study underscore the importance of strengthening the supervisory system and enhancing the competencies of human resources to ensure consistent financial transparency and accountability.